Experiences of reintegration, relapse, and readmission: a qualitative study among patients with alcohol use disorder in Uganda - Mukula, Hillary Mugabo; Ndeezi, Morris; Opondo, Harriet; Ouma, Samuel; Musanje, Khamisi (Frontiers in Public Health, 2025)
IntroductionAlcohol Use Disorder (AUD) is a significant public health concern in Uganda, with many patients experiencing relapses. Despite the implementation of various interventions and support services aimed at managing AUD, a substantial number of patients continue to experience relapses, resulting in frequent readmissions. These relapses and readmissions add additional strain to the already burdened healthcare system. Gaining insight into patients' experiences of relapse can help enhance support services and decrease the likelihood of readmissions.MethodsA descriptive qualitative study examined the relapse experiences of 12 stable AUD patients at Uganda's National Referral Mental Hospital. In-depth interviews were conducted using a semi-structured interview guide, and the data were analyzed thematically through an inductive approach.ResultsThree main themes emerged: causes of relapse, experiences of readmission, and challenges to reintegration. Triggers for relapse included frustration, loneliness, sleep disturbances, negative life events, and peer pressure. Key experiences related to readmission encompassed personal reflection, mastery of treatment, and involuntary admissions. Challenges to reintegration focused on stigma, social disconnection, and feelings of being an outsider.DiscussionThe findings offer valuable insights for enhancing reintegration support services, which may help reduce relapse rates and improve outcomes for AUD patients in Uganda.